Accretion in active galactic nuclei and disk‐jet coupling. Issue 1 (February 2016) - Czerny, B.; You, B.
Abstract: We review the current state of understanding how accretion onto a black hole proceeds and what the key elements needed to form relativistic jets are. Theoretical progress is severely undermined by the lack of thorough understanding of the microphysics involved in accretion discs and in the formation of jets, particularly in the presence of strong magnetic fields. Therefore, all proposed solutions are still models that need to be validated by observational constraints. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)